Leishmania major and Trypanosoma lewisi infection in invasive and native rodents in Senegal. - Cécile Cassan; Christophe A Diagne; Caroline Tatard; Philippe Gauthier; Ambroise Dalecky; Khalilou Bâ; Mamadou Kane; Youssoupha Niang; Mamoudou Diallo; Aliou Sow; Carine Brouat; Anne-Laure Bañuls (Public Library of Science (PLoS), 2018)
Bioinvasion is a major public health issue because it can lead to the introduction of pathogens in new areas and favours the emergence of zoonotic diseases. Rodents are prominent invasive species, and act as reservoirs in many zoonotic infectious diseases. The aim of this study was to determine the link between the distribution and spread of two parasite taxa (Leishmania spp. and Trypanosoma lewisi) and the progressive invasion of Senegal by two commensal rodent species (the house mouse Mus musculus domesticus and the black rat Rattus rattus). M. m. domesticus and R. rattus have invaded the northern part and the central/southern part of the country, respectively. Native and invasive rodents were caught in villages and cities along the invasion gradients of both invaders, from coastal localities towards the interior of the land. Molecular diagnosis of the two trypanosomatid infections was performed using spleen specimens. In the north, neither M. m. domesticus nor the native species were carriers of these parasites. Conversely, in the south, 17.5% of R. rattus were infected by L. major and 27.8% by T. lewisi, while very few commensal native rodents were carriers. Prevalence pattern along invasion gradients, together with the knowledge on the geographical distribution of the parasites, suggested that the presence of the two parasites in R. rattus in Senegal is of different origins. Indeed, the invader R. rattus could have been locally infected by the native parasite L. major. Conversely, it could have introduced the exotic parasite T. lewisi in Senegal, the latter appearing to be poorly transmitted to native rodents. Altogether, these data show that R. rattus is a carrier of both parasites and could be responsible for the emergence of new foci of cutaneous leishmaniasis, or for the transmission of atypical human trypanosomiasis in Senegal.